Molecular biomarkers for vascular cognitive impairment and dementia: the current status and directions for the future - Satoshi Hosoki; Perminder S. Sachdev (2024)
Centre for Healthy Brain Ageing, Discipline of Psychiatry and Mental Health, School of Clinical Medicine, Faculty of Medicine and Health, University of New South Wales, Sydney, Australia Department of Neurology, National Cerebral and Cardiovascular Center, Osaka, Japan *Correspondence to: Satoshi Hosoki, MD, PhD, [email protected]. This is an open-access article distributed under the terms of the Creative Commons Attribution-Noncommercial-Share Alike 4.0 Unported, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.